Evaluating the risk factors for complications of patients with oral and maxillofacial space infections: a systematic review and meta-analysis - Yixiao Wang; Zizhan Li; Yang Chen; Hao Zhang; Babo Zhang; Shuguang Hou; Zhongjun Shao; Hao Guan (BMC Oral Health)
Abstract Objective This study sought to perform a meta-analysis of the risk factors for the complications of oral and maxillofacial space infections (OMSI), aiming to provide insights for identifying cases at elevated risk and facilitating the further clinical prevention strategies. Methods A comprehensive search of international (PubMed, Web of Science, Cochrane Library and CTdatabase) and Chinese (CNKI, Wanfang and VIP) databases was conducted through August 2024. The identified literature was assessed for quality, and meta-analysis was conducted using RevMan 5.0 software. Results A total of 12 studies were included, comprising 2,205 participants, among whom 417 experienced complications, yielding a complication rate of 18.91%. Meta-analysis identified the following as significant risk factors for OMSI-associated complications: age [odds ratio(OR): 1.59; 95% confidence interval(CI): 1.33–1.90], body temperature upon admission (OR: 2.97; 95% CI: 2.03–4.33), diabetes mellitus (OR: 2.70; 95% CI: 2.03–3.60), multiple space infections (OR: 2.90; 95% CI: 1.98–4.25), white blood cell (WBC) count (OR: 1.86; 95% CI: 1.48–2.35), neutrophil (NEUT) count (OR: 2.50; 95% CI: 1.60–3.93), and C-reactive protein (CRP) level (OR: 1.01; 95% CI: 1.00–1.01). Conclusion The incidence of OMSI-associated complications is high. Independent risk factors include advanced age, elevated body temperature on admission, diabetes mellitus, involvement of multiple anatomical spaces, and increased levels of WBC, NEUT, and CRP. These factors may exacerbate infection severity, amplifying the risks of complications such as mediastinitis or sepsis. Therefore, it is crucial to closely monitor patients with these risk factors and implement early interventions to attenuate the incidence of OMSI-associated complications and enhance patient outcomes. While our findings provide valuable insights into risk factors for OMSI-related complications, several limitations—including the predominance of retrospective study designs, heterogeneity in diagnostic criteria and biomarker thresholds—may affect generalizability. Future large-scale and high-quality studies are needed to further validate these findings. Clinical trial number Not applicable.